Colorectal Cancer Methods and Protocols - Powell, Steven M.; Powell, Steven M. (Methods in Molecular Medicine,, 2001)
Colorectal cancer is a common and highly lethal cancer once spread whose treatment is improving as we gain a better understanding of its development. In Colorectal Cancer: Methods and Protocols, Steven M. Powell, MD, has assembled a hands-on collection of cutting-edge molecular methods for studying this solid tumor. These readily reproducible techniques range from gross microdissection of specimens to specific molecular analyses. Here both the novice and experienced researcher will find productive chromosomal analyses, including comparative genomic hybridization and FISH assays, and revealing gene expression analyses, including immunohistochemical assays, Western blotting, and microarray assays. Also presented are mutational analyses of colon tumors and blood samples to determine whether specific patients have inherited a significant predisposition to colorectal cancer. Each method is described in step-by-step detail by an established expert to ensure robust experimental results, and all are accompanied by detailed notes on pitfalls to avoid. Eminently practical, with each technique presented as if the expert in the field who had perfected it were guiding the investigator, Colorectal Cancer: Methods and Protocols provides cancer investigators with a gold standard collection of all the key genetic, cellular, and molecular biological methods for analyzing colon cancer today.